Effects of background and contour luminance on the hue and brightness of the Watercolor effect. (March 2018) - Gerardin, Peggy; Dojat, Michel; Knoblauch, Kenneth; Devinck, Frédéric
Highlights: High inner-contour luminance gave assimilation for hue but contrast for brightness. High background luminances enhanced the hue but reduced the brightness effect. The results suggest different mechanisms of brightness and coloration in the WCE. Abstract: Conjoint measurement was used to investigate the joint influences of the luminance of the background and the inner contour on hue- and brightness filling-in for a stimulus configuration generating a water-color effect (WCE), i.e., a wiggly bi-chromatic contour enclosing a region with the lower luminance component on the exterior. Two stimuli with the background and inner contour luminances covarying independently were successively presented, and in separate experiments, the observer judged which member of the pair's interior regions contained a stronger hue or was brighter. Braided-contour control stimuli that generated little or no perceptual filling-in were also used to assess whether observers were judging the interior regions and not the contours themselves. Three nested models of the contributions of the background and inner contour to the judgments were fit to the data by maximum likelihood and evaluated by likelihood ratio tests. Both stimulus components contributed to both the hue and brightness of the interior region with increasing luminance of the inner contour generating an assimilative filling-in for the hue judgments but a contrast effect for the brightness judgments. Control analyses showed negligible effects for the order of the luminance of the background or inner contour on the judgments. An additive contribution of both components was rejected in favor of a saturated model in which the responses depended on the levels of both stimulus components. For the hue judgments, increased background luminance led to greater hue filling-in at higher luminances of the interior contour. For the brightness judgments, the higher background luminance generated less brightness filling-in at higher luminances of the interior contour. The results indicate different effects of the inner contour and background on the induction of the brightness and coloration percepts of the WCE, suggesting that they are mediated by different mechanisms.